2013
DOI: 10.1186/1749-8090-8-108
|View full text |Cite
|
Sign up to set email alerts
|

11 cm Haughton D left cervical aortic arch aneurysm

Abstract: A 56 year old Caucasian man presented with sudden loss of consciousness while driving and was found to have an 11 cm Haughton D type left cervical aortic arch aneurysm with normal brachiocephalic branching and normal descending thoracic laterality but with considerable tortuosity and redundancy of aortic arch. The aneurysm arose between the left common carotid artery and the left subclavian artery. It compressed and stretched the left common carotid artery, compressed the pulmonary trunk and the left pulmonary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Two other approaches are the median sternotomy with extension to the bilateral supraclavicular regions and the clamshell incision (through bilateral thoracotomies in the anterior third intercostal space with transverse sternotomy), both of which are not cosmetically appealing and are associated with postoperative incisional pain. All cases that have been reported utilized some sort of an interposition graft to restore the continuity between the arch and descending aorta after excising the diseased portion of the cervical arch . The subclavian artery is usually preserved and the re‐intervention rate is low.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two other approaches are the median sternotomy with extension to the bilateral supraclavicular regions and the clamshell incision (through bilateral thoracotomies in the anterior third intercostal space with transverse sternotomy), both of which are not cosmetically appealing and are associated with postoperative incisional pain. All cases that have been reported utilized some sort of an interposition graft to restore the continuity between the arch and descending aorta after excising the diseased portion of the cervical arch . The subclavian artery is usually preserved and the re‐intervention rate is low.…”
Section: Discussionmentioning
confidence: 99%
“…All cases that have been reported utilized some sort of an interposition graft to restore the continuity between the arch and descending aorta after excising the diseased portion of the cervical arch. [6][7][8][9][10] The subclavian artery is usually preserved and the re-intervention rate is low. These data are derived from the adult literature where tissue growth is not expected.…”
Section: Surgical Techniquementioning
confidence: 99%
“…The aetiology of CAA is uncertain, but the most commonly propagated theories involve the fourth primitive aortic arch, which normally gives rise to the aortic arch. Some authors suggest that it regresses, with the aorta instead arising from the third arch, while others suggest that it fails to migrate inferiorly when fully formed 6. A less commonly postulated theory is that the second arch develops into the aortic arch, with persistence of the first arch as the proximal internal carotid artery 7…”
Section: Discussionmentioning
confidence: 99%
“…Specific cardiac anomalies associated with CAA include ventricular septal defect, tetralogy of Fallot and pulmonary atresia 9. Other complications of CAA include aortic aneurysms, which arise in approximately 20% of cases,10 and atherosclerosis, with a consequent risk of cerebrovascular disease 6…”
Section: Discussionmentioning
confidence: 99%
“…Isolated or long-segment or multiple coarctation have been reported in CAA [1,2], and due to common longsegment involvement, it has been suggested that the reason for development of coarctation may be different in CAA rather than the usual constriction caused by the ductal ligament [2]. CAA is believed to occur due to persistence of the third brachial arch and regression of the fourth [2,4,5], whereas others advocate a retained normally derived arch in the cervical region [1,2,5]. Mullens and colleagues [6] stated the requirement for the apex of the arch to be in the cervical position, separate origin of the contralateral carotid artery, and aberrant origin of the contralateral subclavian artery from the descending aorta and retroesophageal descending aorta crossing contralateral to the side of the aortic arch to qualify as CAA complex.…”
Section: Commentmentioning
confidence: 99%